BLENDED LEARNING AND WEB TECHNOLOGIES FOR ICT COMPETENCE FORMATION IN ENGLISH LANGUAGE PEDAGOGY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Blended learning has become a crucial component in modern educational settings, integrating traditional face-to-face instruction with digital and web-based technologies. This approach is particularly significant in English language pedagogy, where students need to develop not only linguistic proficiency but also digital competencies essential for the 21st century. The formation of ICT competence among future English language teachers is imperative, as it enables them to effectively utilize online resources, web applications, and virtual learning environments. This study explores the role of blended learning and web technologies in fostering ICT competence among English language learners in higher education institutions in Uzbekistan. By analyzing the impact of various digital tools, web platforms, and pedagogical strategies, this paper aims to provide insights into how educators can optimize technology integration in language instruction. The findings indicate that blended learning enhances student engagement, promotes self-directed learning, and improves digital literacy skills, ultimately preparing students for the demands of a technology-driven educational landscape.